A survey of sports and rehabilitation professionals on foam rolling applications, contraindications, and adverse events - does the science reach professionals’ perceptions? - Bartsch, Katja; Slomka, Gunda; Baumgart, Christian; Offermann, Christina; Schleip, Robert; Freiwald, Jürgen; Klingler, Werner; Egner, Christoph; Wilke, Jan; Hoppe, Matthias W. (Frontiers in Physiology, 2025)
Foam Rolling (FR) is a type of self-massage used in sports and rehabilitation. The evidence on its effects has significantly increased in recent years; however, the extent to which novel research findings on FR have been implemented in practice remains unknown. Thus, we aimed to survey and document responses on the application, contraindications, and adverse events of FR among German-speaking sports and rehabilitation professionals. A cross-sectional online survey was conducted, which included 21 items relating to four key topics: (i) participant characteristics, (ii) FR application parameters, (iii) contraindications, and (iv) adverse events. Overall, 776 participants consented to participate. 68.6% of respondents indicated using FR in their practice. Average duration of FR was recommended at 3.2 min per body region. Smooth rollers were primarily used (82.9%). Pursued goals and observed effects were largely congruent and subjective methods were mainly used to assess effects. 90.9% of FR-users considered contraindications in practice, with pain being the most commonly noted factor. Headaches and tissue inflammation were the most reported side effects. While 32.4% believed that no adverse events can be expected, most respondents found however adverse events such as tissue inflammation plausible. An assumed lack of scientific evidence for positive effects was the most frequently cited reason for non-use of FR. Although our results demonstrate congruency between research findings and practical application across various parameters, researchers and practitioners should collaborate closely to disseminate knowledge, establish guidelines, and expand the FR evidence base, particularly regarding adverse events.